The GAMBARAN OPTIMISME ANAK PADA PERCERAIAN ORANG TUA: The Picture Of The Childl's Optimism On The Divorce Of The Parents - Jessica Salim; Mira wati (Psikologi Prima, 2022)
Family is the first place for individuals which becomes the primary place for someone to learn and instill life values. Living in a family will only sometimes go according to what we expect, but other things will appear that intentionally or unintentionally will become obstacles. If you have made all the prevention efforts and solutions to remove existing obstacles but are unsuccessful, the way to do this is through a divorce. According to Yusuf (2004), parental divorce is a family situation that is not harmonious, unstable, or messy. The condition of children who experience divorce will have the ability to position themselves or have a habit of dealing with problems that occur. Therefore, optimism is the ability of a child to deal with the situation they are experiencing or the tendency to face a problem in thinking in a good or positive direction. So divorce will make children feel devastated, and some will feel pessimistic. However, some children will feel a rift in their parent's relationship, which results in a divorce, and will feel optimistic about what happened to them. By feeling optimistic, the child can adjust and adapt to an environment that will experience drastic changes. The research method used in this study is qualitative, and the method used is a literature study.